1992
DOI: 10.1302/0301-620x.74b1.1732256
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene wear in uncemented knee replacements

Abstract: PATIENTS AND METHODS A series of 96 patients underwent 108 primary total knee replacements using the uncemented PCA knee. We selected patients under 60 years of age and fit, active patients ofless than 70 for this type ofarthroplasty. Their ages ranged from 19 to 69 years (mean 51). The primary pathology was rheumatoid arthritis in 73 of the knees and osteoarthritis in 35. All the operations were per

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(37 citation statements)
references
References 11 publications
3
34
0
Order By: Relevance
“…The effect of contact pressure on wear has been previously reported for unidirectional motion pin-on-plate studies [2] and the effect of conformity on surface area on wear has also been reported in the hip [26]. This approach to reducing surface wear by reducing conformity and wear area contradicts the thinking of the 1980s and 1990s [5,6,8,19] that led to more conforming designs in order to avoid the risk of delamination and fatigue following oxidative degradation. The conformity of fixed-bearing knee designs has generally increased over the last two decades, partly to address concerns over fatigue failure and delamination due to oxidative degradation of polyethylene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of contact pressure on wear has been previously reported for unidirectional motion pin-on-plate studies [2] and the effect of conformity on surface area on wear has also been reported in the hip [26]. This approach to reducing surface wear by reducing conformity and wear area contradicts the thinking of the 1980s and 1990s [5,6,8,19] that led to more conforming designs in order to avoid the risk of delamination and fatigue following oxidative degradation. The conformity of fixed-bearing knee designs has generally increased over the last two decades, partly to address concerns over fatigue failure and delamination due to oxidative degradation of polyethylene.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the failure of gamma-in-air sterilization polyethylene in knees was due to oxidative degradation, causing a reduction in mechanical properties and fatigue failure, which has been described as delamination wear [5,6,8,19]. Oxidative degradation also increases surface wear and osteolysis [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delamination of PCA total knees has been attributed to hot pressing of the polyethylene surface coupled with the low conforming surface (Bloebaum et al 1991, Collier et a). 1991, Engh et al 1992, Jones et al 1992. Hot pressing leads to reduced crystallinity of the polyethylene in a well defined zone, extending to approximately 1 mm below the surface (Bloebaum et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…[4], which is 72 months. There were also studies on the massive delaminating of the polyethylene occurred earlier [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%